Blended Learning Model Based on Google Classroom on The Ability to Read Short Stories in Sundanese Subjects - Ropiah, Opah; Pebriyanti, Devi; Syahrul, Ninawati; Sunarti, Sastri; Stephen, Jeannet; Masduki, Aam (Universitas Negeri Makassar, 2023)
The blended learning model based on Google Classroom is a learning model that uses the Google Classroom application to make it easier for teachers and students in the learning process. This study aimed to determine the effect of the blended learning model based on Google Classroom on student learning outcomes in reading short stories in Sundanese subjects. The method used in this research is the experimental method with a pretest-posttest control group design. The population in this study were students of class 1 Kramatmulya Public Junior High School. The sample in this study were students of class VIII.B as the experimental class and class VIII.C as the control class—data collection through observation, tests, and documentation. The analysis technique used the validation test, normality test, homogeneity test, and independent t-test. The results of this study were: 1) the ability of students who had reached the minimum completeness criteria in reading short stories before using the blended learning model, namely 13.33% in the experimental class and 6.67% in the control class; 2) the ability of students who have reached the minimum completeness criteria in reading short stories after using the blended learning model based on Google classroom, namely 66.67% in the experimental class and 20.00% in the control class; and 3) based on the results of the pretest and posttest and the independent t-test, the google classroom-based blended learning model influences student learning outcomes in the ability to read short stories